Лінгвістичний алгоритм керування об’єктом з неповною визначеністю - Галай, Василь Миколайович (НТУ "ХПІ", 2010)
Synthesis of the linguistic control algorithm by modes robots of an automation object with incomplete informational definiteness in which quality it is used rotor the resistance furnace resistance.
The linguistic control algorithm the object with incomplete definition
Keywords: автоматизація; піч вакуумна; піч роторна; скло кварцеве; модель математична; множини нечіткі; оцінка експертна; плавлення